Improving school effectiveness - Woods, David (Buckingham : Open University Press, 2001)
This work sets out to answer questions such as, what have we learned after three decades of research into school effectiveness? What can we say with confidence about how schools improve? It reviews findings from seminal international work.
A is for Action research -- Acts of unexpected kindness -- Advanced Skills Teacher (AST) --Appreciative enquiry -- Assessment for Learning (AfL) -- Attention to detail -- B is for Backward (or forward) looking organizations -- Balance of skills in the leadership team -- Breakfast clubs -- Buildings and the environment - C is for Capability -- Case studies - Chains - Challenge - Change -- Classroom interventions -- Closing the attainment gap - Coaching -- Common language -- Continuing Professional Development (CPD) -- Critical friendship -- Culture of schools - Curriculum -- D is for Data - Delegation - Differentiation - Display -- E is for Energy creators - Engagement -- Essential tasks of successful leaders - Ethos - Examinations -- Experiences, enrichment and entitlements -- F is for Failure (as an essential ingredient of success) -- Family of schools - Federations -- Fischer Family Trust (FFT) -- Forums for teaching and learning -- Four stages of headship -- G is for Good to great - Governors -- Grammar of school improvement -- H is for Headteachers spending their evenings and weekends balancing work and home life -- Headteachers teaching, learning and assessing - Homework - Hope - Hyacinths -- I is for Inclusion -- Induction of ... - Inspection -- In-School Variation (ISV) -- INSET (or occasional days) -- Interim Executive Board (IEB) -- Interventions to raise school standards - J is for Job descriptions - Judgement - K is for Kes factor -- Key expenditures of time by school leaders -- Knowledge creation and innovation -- L is for Lavatories - Leadership - Learning -- Learning narratives -- Learning styles -- Learning walks -- Lesson plans - Library - Literacy -- Local Leader of Education (LLE) -- Lunch hour -- M is for Marking - Meetings - Mindset -- Moral purpose -- N is for National Leader of Education (NLE) and National Support School (NSS) -- National teaching schools -- Numeracy and the development of mathematical language -- O is for Optimism -- P is for Parents and carers - Partnerships - Pastoral -- Peer learning -- Peer review -- Performance management -- Personalized learning -- Planning for school improvement -- Progress -- Professional learning community -- Q is for Quality assurance and quality control - Questions -- Quick wins - Quotations - R is for RAISEonline - Raising Attainment Plan (RAP) - Research - Residentials - S is for Seating plans - Self-evaluation - School-to-school support - Singing from the same song sheet - Sitting on the wall not the fence -- Skalds not scolds - Spiritual, moral, social and cultural education (SMSC) - Special educational needs (SEN) - Specialist leader of education (SLE) - Staff appointments - Staff development - Staff handbook - Storytelling - Student voice - Success - Support staff - T is for Target setting - Teach first - Teacher credibility - Teachers and teaching (and learning) - Teachers talking about teaching - Teams and teamwork - Time management - Times Educational Supplement (TES) - Timetable - Transition - Trust - Tutor and tutor period - U is for Uniforms-University links - V is for Values - Virtual Learning Environment (VLE) - Vision and vision statements - W is for World class - X is for eXtra -curricular activities - X factor - X: wrong - Y is for Year heads - Yes we can - YouTube - Z is for Zone - Zenith.
Includes bibliographical references and index.
Keywords: SCHOOL IMPROVEMENT PROGRAMS